The relationship between the logo and tagline and their influence on the customer buying decision : a case study of nike brand - 505894 Vincent, Eng Choon Heng; Noor Azmi Mohamad; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2010)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2010